2019
DOI: 10.1186/s12978-019-0689-6
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric emergency simulation training course: experience of a private-public partnership in Brazil

Abstract: Background Lack of skills on how to diagnose and manage obstetric emergencies contribute to substandard institutional care and preventable maternal deaths in Brazil. Simulation-based obstetric emergency team training can reduce adverse maternal outcomes. However, this type of training is expensive and not widely available, especially in low resource settings. We present the experience of a private-public partnership that offered a two-day obstetric emergency simulation-training course to hundreds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Therefore, these findings imply that public-private partnerships had the strongest relationship with the performance of the Nakuru County Assembly Wards. These findings are supported by those of Siaulys et al (2019) who found that there was a strong relationship between public-private partnerships and the performance of public-sector organizations. Partnering with private organizations helped public sector organizations to meet their mandates such as service delivery to the public.…”
Section: Correlation Analysissupporting
confidence: 73%
“…Therefore, these findings imply that public-private partnerships had the strongest relationship with the performance of the Nakuru County Assembly Wards. These findings are supported by those of Siaulys et al (2019) who found that there was a strong relationship between public-private partnerships and the performance of public-sector organizations. Partnering with private organizations helped public sector organizations to meet their mandates such as service delivery to the public.…”
Section: Correlation Analysissupporting
confidence: 73%
“…one China [27], three India [32,44,48], one Brazil [40] and one Mexico [41]). Six of the extracted articles were from High income countries including (three Europe [22,49], one Australia [23], one United states [29], one Spain [34], one Netherlands [35] and one Saudi Arabia [36]).…”
Section: Resultsmentioning
confidence: 99%
“…The initial search yielded 5,168 unique records (Figure 1). After screening the titles and abstracts, the full text of 198 potentially eligible studies was screened, and 38 studies were included in this review (Al-Kadri et al, 2014;Amod & Brysiewicz, 2017;Andreatta et al, 2011;Andrighetti et al, 2012;Burns et al, 2019;Dawood et al, 2021;Evans et al, 2014;Garcia et al, 2012;Ghosh et al, 2019;Goldsworthy et al, 2019;Gray & Cavner, 2017;Jayanna et al, 2016;Joudeh et al, 2021;Komorowski et al, 2017;Kordi et al, 2015;Kordi et al, 2016;Latuska et al, 2019;Lei et al, 2019;Low et al, 2008;Low et al, 2012;Luegenbiehl, 1997;Miner, 2020;Moudi et al, 2019;Nilsson et al, 2014;Nishimwe et al, 2021;Rao et al, 2019;Siaulys et al, 2019;Sorensen et al, 2009;Stitely et al, 2011;Sukprasert et al, 2006;Varanelli et al, 2019;Weiler et al, 2018;Wong et al, 2016;Zehler & Musallam, 2021).…”
Section: Resultsmentioning
confidence: 99%